SOCIAL MAPPING AS AN EDUCATIONAL TOOL FOR THE RECOGNITION OF GEO HISTORICAL PROCESSES IN LOCAL SPACES. - Niño Jaimes Maria (DIALÉCTICA, 2025)
Talking about educational tools as the central axis for the learning areas where the multidisciplinary integration of learning knowledge and knowledge is sought, allows promoting the comprehensive teaching process in the student community. That is to say, the innovation of social cartography as an innovative element in the recognition of the geographic space, an activity that will take place in a strategic scenario where some conceive information, space and territory. Analyze social cartography as a basis for understanding and applying educational morphology as a tool and resource in education. In this sense, cartography, where the vision of the future and the fight tactic are traced as a physical environmental space, and geographically delimited where a system of interrelationships takes place that produce a set of interpersonal relationships based on the needs of the community. Social cartography has a set of graphic representations that improves the understanding and comprehension of the representations where they offer information and know how to transform social problems in the study scenarios. The realization of this study is proposed with the intention of implementing social cartography as a pedagogical tool that serves to recognize geohistorical processes in local spaces, a powerful work tool considered in the educational field of new practices in the execution and its purpose is that students have knowledge that facilitates the management of information in the different processes and effective teaching-learning advances.